GC-MS ANALYSIS OF BIOACTIVE COMPONENTS IN THE ETHANOLIC AND METHANOLIC EXTRACT OF Syzygium cumini - NEHA ATALE,; VIBHA RANI, (International Journal of Pharma and Bio Sciences, 2013)
In developing countries, high rate of mortality was found due to diabetes and other cardiovascular diseases etc. Plants are used worldwide as a source of many powerful drugs. The present investigation was carried out to determine the bioactive phytoconstituents (polyphenols and essential oils) in the ethanolic (ESE) and methanolic (MSE) extracts of seeds of S. cumini by GC-MS analysis. 34 major compounds were found in MSE such as 5,10-Dichloro-5,10-Dimethyltricyclo [7.1.0.0 (4-6)] decane (7.93%), Tetradecanoic acid (13.08%) α-Caryophyllene (4.52%), 1,10-Decandiol (19.83%), Bicyclo (4.4.O) Decane (1.37%), Octadienol (1.31%), Cadinene (0.24%), 2-Furancarboxaldehyde 5-(hydroxymethyl) (17.11%), Oxirane etc. and 25 components were found in ESE such as Nondecanoic acid (10.85%), Decahydro-4A-Methyl-1-Methylene-7-(1-methylethenyl) (6.81%), 12-Methyl-E,E-2,13-octadecadien-1-ol (19.83%) Furanone dihydroxy-2-Methyl (4.19%), and Caryophyllene oxide (1.32%), Isogeraniol (0.50%) etc. were found in less amount in ESE. Thus, we found MSE as a most potent and enriched extract than that of ESE and can be used for the treatment of various hazardous diseases.